Imaging of Occupational and Environmental Disorders of the Chest - Gevenois, Pierre Alain; de Vuyst, Paul (Diagnostic Imaging,, 2006)
The spectrum of occupational and environmental diseases has changed markedly during the past decade. Pneumoconiosis is still a common cause of chronic lung disease but the concept has evolved to encompass reactions of the lung to chemicals and organic or inorganic dust. Furthermore, new industrial processes have led to the production and use of a wide range of chemicals, metals, and alloys, an increasing number of which, including man-made organic particles, are reported to cause interstitial lung disease in exposed workers. Thus, while the workforce in coal mining and asbestos handling has decreased, new groups of workers are at risk of exposure to large amounts of mineral and metallic dusts that may induce pneumoconiosis. This well-illustrated book, written by internationally acclaimed experts, provides an up-to-date and comprehensive approach to modern imaging of environmental and occupational diseases of the chest. The first part of the book addresses the basic knowledge required to understand imaging in this context, while the second focuses on the imaging results achieved in a variety of specific disorders. There is particular emphasis on the role of thin-section computed tomography since this technique facilitates the detection of early subclinical abnormalities.